Association of reproductive traits with captive‐ versus wild‐sourced birds in trade - Oscar Morton; Brett R. Scheffers; Torbjørn Haugaasen; David P. Edwards (Conservation Biology, 2023)
The wildlife trade is a billion‐dollar global business, involving millions of people, thousands of species, and hundreds of millions of individual organisms. Unravelling whether trade targets reproductively distinct species and whether this preference varies between captive‐ and wild‐sourced species is a crucial question. We used a comprehensive list of all bird species traded, trade listings and records kept in compliance with the Convention on International Trade in Endangered Species (CITES), and a suite of avian reproductive parameters to examine whether wildlife trade is associated with particular facets of life history and to examine the association between life‐history traits and captive‐ and wild‐sourced traded volumes over time. Across all trade, CITES listing, and CITES trade, large birds were more likely to be traded and listed, but their longevity and age at maturity were not associated with CITES listing or trade. We found species across almost the full range of trait values in both captive and wild trade between 2000 and 2020. Captive trade volumes clearly associated with relatively longer lived and early‐maturing species; these associations remained stable and largely unchanged over time. Trait–volume associations in wild‐sourced trade were more uncertain. Only body mass had a clear association, and it varied from negative to positive over time. Although reproductive traits were important in captive‐sourced trade, species‐level variation dominated trade, with even congeneric species varying greatly in volume despite similar traits. The collection and incorporation of trait data into sustainability assessments of captive breeding facilities are crucial to ensure accurate quotas and guard against laundering.